Study on the Application of Doxorubicin-Loaded Magnetic Nanodrugs in Targeted Therapy of Liver Cancer - Lei Wang; Liping Liang; Shuzhen Shi; Chao Wang (Applied Bionics and Biomechanics)
Doxorubicin (DOX) has been widely recognized as effective in anticancer therapy; however, the additional organ toxicity and low targeting of DOX in antitumor activity remains unaddressed. The aim of this study was to use the drug carrier dextran/polylactic acid (DEX/PLA) and paramagnetic Fe3O4 to improve the targeting of DOX in liver cancer treatment while reducing its potential organ toxicity. Our experimental results show that the combination drug (Fe3O4@DEX/PLA-DOX) exhibits strong hepatocarcinogenic inhibition and low cytotoxicity and that this modified drug provides a better option for clinical liver cancer treatment.